2013
DOI: 10.1111/1574-6941.12084
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community potentially responsible for acid and metal release from an Ostrobothnian acid sulfate soil

Abstract: Soils containing an approximately equal mixture of metastable iron sulfides and pyrite occur in the boreal Ostrobothnian coastal region of Finland, termed ‘potential acid sulfate soil materials’. If the iron sulfides are exposed to air, oxidation reactions result in acid and metal release to the environment that can cause severe damage. Despite that acidophilic microorganisms catalyze acid and metal release from sulfide minerals, the microbiology of acid sulfate soil (ASS) materials has been neglected. The mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 33 publications
0
45
0
Order By: Relevance
“…Details of the study area (Åström et al, 2007;Boman et al, 2010) and the physicochemical parameters of the Risöfladan experimental field (Wu et al, 2013) have been previously reported. In brief, the soil below the plow layer consisted of clay with a well-developed structure with an abundance of iron oxide coatings.…”
Section: Study Site and Samplingmentioning
confidence: 99%
See 4 more Smart Citations
“…Details of the study area (Åström et al, 2007;Boman et al, 2010) and the physicochemical parameters of the Risöfladan experimental field (Wu et al, 2013) have been previously reported. In brief, the soil below the plow layer consisted of clay with a well-developed structure with an abundance of iron oxide coatings.…”
Section: Study Site and Samplingmentioning
confidence: 99%
“…In brief, the soil below the plow layer consisted of clay with a well-developed structure with an abundance of iron oxide coatings. The sulfur content was in the order of ≥ 0.2% (wt/vol) and the pH was~4 in all soil samples due to significant sulfide oxidation (Wu et al, 2013). In total, 24 cores were used in preliminary studies, method development, and the five cores for the experiments reported here.…”
Section: Study Site and Samplingmentioning
confidence: 99%
See 3 more Smart Citations